Mortimer's bread bin - Aiken, Joan; Blake, Quentin (Barn Owl Books London, 2001)
Mortimer the Raven is causing yet more chaos and mayhem in Rumbury town. Things get even worse when Arabel takes Mortimer roller-skating with her three nasty cousins Cindy, Mindy and Lindy